Role of the innate immune system in the pathogenesis of multiple sclerosis - Gandhi, Roopali; Laroni, Alice; Weiner, Howard L. (Journal of neuroimmunology, 2010)
Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease with heterogeneous clinical presentations and course. MS is considered to be a T cell mediated disease but in recent years contribution of innate immune cells in mediating MS pathogenesis is being appreciated. In this review, we have discussed the role of various innate immune cells in mediating MS. In particular, we have provided an overview of potential anti-inflammatory or pro-inflammatory function of DCs, microglial Cells, NK cells, NK-T cells and gamma delta T cells along with their interaction among themselves and with myelin. Given the understanding of the role of the innate immune cells in MS, it is possible that immunotherapeutic intervention targeting these cells may provide a better and effective treatment.